A review and critique of content analysis as a methodology for inquiring into IC disclosure. Issue 2 (8th April 2014) - Dumay, John; Cai, Linlin
Abstract : Purpose: – The purpose of this paper is to review and critique the current status of content analysis (CA) as a research method for inquiring into intellectual capital disclosure (ICD) to determine if CA has a continued role to play in developing new intellectual capital (IC) knowledge. Design/methodology/approach: – In all, 110 articles utilising CA as a research methodology for inquiring into ICD are analysed. The research is developed in line with other articles critically investigating IC research conducted by Guthrie et al. (2012), Dumay and Garanina (2013) and Dumay (2014). To help understand the impact of CA research articles, the data set is supplemented by including citation data from Google Scholar. The authors also differentiate the paper from other IC research reviews by critically examining the findings and implications of the articles analysed. Findings: – The authors do not hold a very positive view on future research which does not substantially depart from the plethora of articles examining ICD using annual reports as a data source or who do not in some way radically change the approach. The authors are of the view that early research into ICD using CA as a methodology was warranted because there was little knowledge about the pattern of IC disclosure in annual reports and other possible ICD forms. However, the research into ICD using annual reports and other data sources has added little more than prove that companies are unwilling to publicly disclose IC to their stakeholders. While the authors do not hold a positive view on future CA research based on annual reports, the authors do hold out hope that researchers will transform their understanding and application of CA as a research methodology and offer one example of how this might be achieved. Originality/value: – The paper presents a comprehensive critical review of published articles utilising CA as a research methodology for inquiring into ICD along with measuring the impact of the articles using citation data from Google Scholar. Hence, the research and its impacts are simultaneously assessed offering insights into the future role that CA as a research methodology has to play in developing new IC knowledge.